Last updated at Feb. 20, 2019 by Teachoo

Transcript

Ex 6.3, 2 Fill in the blanks with >, < or = sign. (a) (– 3) + (– 6) ______ (– 3) – (– 6) (− 3) + (− 6) = − 3 − 6 Taking − common = −(3 + 6) = −9 (− 3) – (− 6) = − 3 + 6 = 6 – 3 = 3 Since − 9 < 3 ∴ (− 3) + (− 6) < (3) − (− 6) Ex 6.3, 2 Fill in the blanks with >, < or = sign. (b) (– 21) – (– 10) _____ (– 31) + (– 11) (− 21) – (− 10) = −21 + 10 Taking − common = − (21 – 10) = − 11 (− 31) + (− 11) = − 31 – 11 Taking − common = − (31 + 11) = − 42 As 11 < 42 So, − 11 > – 42 ∴ (–21) – (–10) > (–31) + (–11 Ex 6.3, 2 Fill in the blanks with >, < or = sign. (c) 45 – (– 11) ______ 57 + (– 4) 45 – (–11) = 45 + 11 = 56 57 + (–4) = 57 – 4 = 53 Since 56 > 53 ∴ 45 – (–11) > 57 + (–4) Ex 6.3, 2 Fill in the blanks with >, < or = sign. (d) (– 25) – (– 42) _____ (– 42) – (– 25) (− 25) – (– 42) = − 25 + 42 = 42 – 25 = 17 (− 42) – (– 25) = − 42 + 25 Taking - common = – (42 – 25) = –17 Since 17 > – 17 ∴ (− 25) – (–42) > (–42) – (–25)

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.